2005
DOI: 10.1002/ceat.200407139
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Generation and [4+2]‐Cycloaddition of Singlet Oxygen in a Falling‐Film Micro Reactor

Abstract: The presented falling‐film microreactor is suited for the generation and reaction of singlet oxygen for the photo‐oxygenation of olefins and allows for the first time conversions on a preparative scale. Due to the short holdup the concentration of the explosive endoperoxide is low in the whole reactor system and the endoperoxide is reduced to the final product immediately after leaving the reactor. The results show the feasibility of this reaction although the process is not yet optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 9 publications
1
58
0
2
Order By: Relevance
“…Prompted by these encouraging results, a multitude of reactor designs -including microfluidic chip reactors [150], falling-film reactors [151], dual-and triplechannel microreactors [152,153], coil-based devices [154,155], gas-permeable micro-capillary films [156], and tube-in-tube membrane devices [157] -were subsequently applied for the generation and subsequent utilization of 1 O 2 in gas/liquid continuous flow regimes using well-known photosensitizers such as Rose Bengal, methylene blue, and porphyrins. Furthermore, it was shown that porphyrins can be immobilized on the channel wall of a glass microreactor to heterogeneously catalyze the formation of the reactive oxygen species [158].…”
Section: Oxidative Carbon-carbon Coupling Reactionsmentioning
confidence: 98%
“…Prompted by these encouraging results, a multitude of reactor designs -including microfluidic chip reactors [150], falling-film reactors [151], dual-and triplechannel microreactors [152,153], coil-based devices [154,155], gas-permeable micro-capillary films [156], and tube-in-tube membrane devices [157] -were subsequently applied for the generation and subsequent utilization of 1 O 2 in gas/liquid continuous flow regimes using well-known photosensitizers such as Rose Bengal, methylene blue, and porphyrins. Furthermore, it was shown that porphyrins can be immobilized on the channel wall of a glass microreactor to heterogeneously catalyze the formation of the reactive oxygen species [158].…”
Section: Oxidative Carbon-carbon Coupling Reactionsmentioning
confidence: 98%
“…Production of sodium nitrotetrazolate, which is a key ingredient used for formulation of explosives and propellants with high energetics, was recently performed using a microreactor and represents a typical application of this type (Kralj et al, 2005). Other useful applications of microreactors for production of energetic materials, along with an example of producing an endoperoxide using singlet oxygen in a falling film microreactor, are described by Jähnisch and Dingerdissen (2005).…”
Section: Safetymentioning
confidence: 99%
“…De Mello [5] reported the singlet oxygen homogeneous photooxidation of aterpinene in an MR, with Rose Bengal as a photosensitizer. A cycloaddition of singlet oxygen to cyclopentadiene was studied by Jähnisch [6] and co-workers in a falling-film MR. Fukuyama [7] described the [2 + 2] photocycloaddition of various cyclohexenones with vinyl acetates in a glass microflow system. Meyer [8] reported the photosensitized oxidation of citronellol in an MR with light-emitting diodes (LED) as a source of light.…”
Section: Introductionmentioning
confidence: 98%